Regulation of Public Finances in the Czech Republic in Light of Financial Constitutionality - Hulkó, Gábor; Radvan, Michal (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
This chapter deals with the basic features of financial law in the Czech Republic. The authors present Czech financial law using the branch-creating criteria: a specific object of legal regulation, a specific method of regulation, a system coherence of financial law norms, and a social acceptance. As the legal relationships regulated by the financial law are very diverse, the Brno legal school uses two groups of these relationships. The fiscal part of financial law deals with the legal relationships created, implemented, and expired in the process of creating, distribution, and use of public monetary funds. It covers tax law, budgetary law, and public subsidies law. The non-fiscal part of financial law deals with the legal relationships created, implemented, and expired in connection with ensuring the functioning of the monetary and financial system. The non-fiscal part covers monetary and foreign exchange law, financial markets law, gaming law, hallmark law, and public procurement law.KEYWORDS: Financial law, tax law, budget, tax, Czech Republic.